Mathematical Problem-Solving Ability on Arithmetic and Geometric Sequences Using Skill Exercises Combined with SSCS Problem-Solving Model for grade 12 students - BOUDSIT, Oudom; MANOSANE, Anousith; HIPHATPHON, Soulasay; PHOMMANITH, Kamsone; PHETHSOMBATH, Sengdao; VATHANAVONG, Thongthiane; THIPPHAPONE, Kinnaly; VONGSIPASEUTH, Bounmor; KONEPACHITH, Domone; HOUNVILAY, Bounthieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of this research was to evaluate the mathematical problem solving ability of Grade 12 students on arithmetic and geometric sequences after participating in learning activities using practice exercise integrated with the SSCS problem-solving model. The target group consisted of 18 Grade 12 students at Kiettisack International School—KIS Luang Prabang, Luang Prabang Capital, Luang Prabang Province in the academic year 2025-2026. The research instruments consisted of five lesson plans integrated with practice exercises, and a subjective mathematical problem-solving ability test which included five sub tests with two questions each. The data analysis was performed using SPSS V.22.0 software to analyze the mean, standard deviation. The finding were the students demonstrated mathematical problem-solving ability in arithmetic and geometric sequences after participating in learning activities using skill exercises combined with the SSCS problem-solving model. Overall their performance was at a high level with an average score of 2.98 and standardized 0.40 2). When considered by each aspect it was found that students demonstrated the highest level of mathematical problem-solving ability in the ‘’ Solve:s’’ stage with an average score of 3.40 which is at the very good level. The next highest was the ‘’ Search: S’’ stage with an average score 3.19 indicating a good level of ability. The lowest average score was found in the fourth stage ‘’share:S’’ which involves exchanging ideas with an average score of 2.49 representing a moderate level of problem-solving ability. 3). When the average scores of the five sub-tests- 2.73 2.83 3.05 3.00 and 3.28 respectively-were compared it was found that the students showed improvement in their mathematical problem-solving ability on the topic of arithmetic and geometric sequences in a positive direction.